2011
DOI: 10.1186/1479-5876-9-37
|View full text |Cite
|
Sign up to set email alerts
|

Histone modification enhances the effectiveness of IL-13 receptor targeted immunotoxin in murine models of human pancreatic cancer

Abstract: BackgroundInterleukin-13 Receptor α2 (IL-13Rα2) is a tumor-associated antigen and target for cancer therapy. Since IL-13Rα2 is heterogeneously overexpressed in a variety of human cancers, it would be highly desirable to uniformly upregulate IL-13Rα2 expression in tumors for optimal targeting.MethodsWe examined epigenetic regulation of IL-13Rα2 in a murine model of human pancreatic cancer by Bisulfite-PCR, sequencing for DNA methylation and chromatin immunoprecipitation for histone modification. Reverse transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Our study also found that TOP2A was up-regulated twofold after decitabine treatment in adrenocortical cell lines (NCI-H295R and SW13). Thus, epigenetically increasing TOP2A expression with the use of demethylating agents may be an effective strategy for increasing TOP2A expression when using agents which target TOP2A 37 . However, we are not able to experimentally prove this as both of the widely used and authenticated ACC cell lines have high levels of basal TOP2A expression and demethylating agents such as decitabine have an antiproliferative effect in ACC cell lines 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study also found that TOP2A was up-regulated twofold after decitabine treatment in adrenocortical cell lines (NCI-H295R and SW13). Thus, epigenetically increasing TOP2A expression with the use of demethylating agents may be an effective strategy for increasing TOP2A expression when using agents which target TOP2A 37 . However, we are not able to experimentally prove this as both of the widely used and authenticated ACC cell lines have high levels of basal TOP2A expression and demethylating agents such as decitabine have an antiproliferative effect in ACC cell lines 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Histone acetylases/deacetylases, the polycomb group proteins, and HP1 are the key histone protein complexes that influence chromatin accessibility and gene activity. Histone modifications have been linked to the altered expression of several critical genes in pancreatic cancer, including the IL-13 receptor, MUC17, MUC4, MUC1 and MUC2 (Esteller, 2007;Fujisawa et al, 2011;Kitamoto et al, 2011;Vincent et al, 2008;Yamada et al, 2008).…”
Section: Histone Modifications and Pancreatic Cancermentioning
confidence: 99%
“…By ChIP, Ballestar et al [79] have found that the gene-specific profiles of Methyl-CpG binding proteins (MBDs) exist for hypermethylated promoters of breast cancer cells with a common pattern of histone modifications shared. It's interesting that Fujisawa et al [81] found CpG sites in IL-13Rα2 promoter region were not methylated in all pancreatic cancer cell lines studied including IL-13Rα2-positive and IL-13Rα2-negative cell lines and normal cells. On the other hand, histones at IL-13Rα2 promoter region were highly acetylated in IL-13Rα2-positive but much less in receptor-negative pancreatic cancer cell lines.…”
Section: Cancer Epigenomicsmentioning
confidence: 99%